Gnoseology between brain size and bioaccumulation of heavy metals in Gambusia punctata (Poey, 1854) - Argota-Pérez, George (2023)
The purpose of the study was to describe the gnoseology between brain size and metal bioaccumulation in Gambusia punctata (Poey, 1854). In September 2022, sampling was conducted in the lower Almendares River, Havana, Cuba: latitude / 23°06'4.92"; longitude / 82°24'30.41", where 37 individuals (26 females and 11 males) were captured for determination of brain size and bioaccumulation of lead (Pb) and cadmium (Cd). The statistical t-Student test indicated that there was no significant difference (p = 0.44) between males and females according to brain size (1.57±0.09 and 1.59±0.08 mm). Bioaccumulation of Pb was: male = 0.084±0.014; female 0.097±0.022 and for Cd corresponded to: male = 0.085±0.014; female 0.108±0.027). Multiple linear regression analysis between brain size and bioaccumulation of heavy metals indicated, p-value = 0.90 (males) and p-value = 0.35 (females). It was concluded that there was bioaccumulation of Pb and Cd in the brain of individuals of the species G. punctata. Bioaccumulation to Pb was similar in both sexes, although there was greater bioaccumulation to Cd in females. However, Pb and Cd bioaccumulation were not detrimentally related to brain size.